2021
DOI: 10.1136/jmedgenet-2021-108186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pathogenicFBN1variant types on the development of severe scoliosis in patients with Marfan syndrome

Abstract: BackgroundAmong the several musculoskeletal manifestations in patients with Marfan syndrome, spinal deformity causes pain and respiratory impairment and is a great hindrance to patients’ daily activities. The present study elucidates the genetic risk factors for the development of severe scoliosis in patients with Marfan syndrome.MethodsWe retrospectively evaluated 278 patients with pathogenic or likely pathogenic FBN1 variants. The patients were divided into those with (n=57) or without (n=221) severe scolios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Because several studies have demonstrated genotype-phenotype correlations in MFS to date, the phenotype of paraspinal muscles may also differ from case to case with different FBN1 variants. [44–48] Fifth, due to the same reason, the relationship between the severity of spinal deformity and the condition of paraspinal muscles was not investigated, which could reinforce our hypothesis.…”
Section: Discussionmentioning
confidence: 85%
“…Because several studies have demonstrated genotype-phenotype correlations in MFS to date, the phenotype of paraspinal muscles may also differ from case to case with different FBN1 variants. [44–48] Fifth, due to the same reason, the relationship between the severity of spinal deformity and the condition of paraspinal muscles was not investigated, which could reinforce our hypothesis.…”
Section: Discussionmentioning
confidence: 85%
“…Early studies on genotype-phenotype correlation began with the susceptibility to EL and aortic dilatation ( Schrijver et al, 2002 ; Loeys et al, 2004 ). Later studies expanded the studied phenotypes to almost all aspects of the MFS manifestations, including the axial length of the eyeball ( Chen et al, 2021a ), astigmatism of the cornea ( Guo et al, 2021 ), severity of scoliosis ( Taniguchi et al, 2021 ), and incidence of ventricular tachycardia ( Aydin et al, 2013 ). Meanwhile, detailed parameters were applied instead of a broad description of aortic events, such as the aortic root diameters and the aortic stiffness ( Franken et al, 2017 ; Salvi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scoliosis is a sideways curvature of the spine if a Cobb’s angle exceeds 20° on radiographs ( Sponseller et al, 1995 ), which is found in 45%–54% of MFS patients ( Faivre et al, 2007 ; Arnaud et al, 2021a ). Taniguchi et al dissect the genotype-phenotype correlations in MFS already having scoliosis and found that HI variants and variants in the neonatal region were associated with severe scoliosis and faster progression ( Taniguchi et al, 2021 ). Higher systematic scores were observed in the HI group than that in the DN group ( Stark et al, 2020 ).…”
Section: Genotype and Clinical Manifestationsmentioning
confidence: 99%
“…However, AADA associated with spinal deformity is unusual in MFS patients. Because of pain and restrictive ventilatory disturbance in patients as a result of spinal deformity, patients with MFS may be at an increased risk of additional cardiopulmonary damage while undergoing a thoracotomy or having repeated pneumothoraxes ( 8 ). Moreover, severe spinal deformity affects surgical intervention, aortic surgery in these patients is challenging.…”
Section: Discussionmentioning
confidence: 99%